Machine learning models for Parkinson’s disease detection and stage classification based on spatial-temporal gait parameters - Ferreira, Marta Isabel A.S.N; Barbieri, Fabio Augusto; Moreno, Vinícius Christianini; Penedo, Tiago; Tavares, João Manuel R.S. (Gait & posture, 2022)
Parkinson’s disease (PD) is a chronic and progressive neurodegenerative disease with no cure, presenting a challenging diagnosis and management. However, despite a significant number of criteria and guidelines have been proposed to improve the diagnosis of PD and to determine the PD stage, the gold standard for diagnosis and symptoms monitoring of PD is still mainly based on clinical evaluation, which includes several subjective factors. The use of machine learning (ML) algorithms in spatial-temporal gait parameters is an interesting advance with easy interpretation and objective factors that may assist in PD diagnostic and follow up. This article studies ML algorithms for: i) distinguish people with PD vs. matched-healthy individuals; and ii) to discriminate PD stages, based on selected spatial-temporal parameters, including variability and asymmetry. Gait data acquired from 63 people with PD with different levels of PD motor symptoms severity, and 63 matched-control group individuals, during self-selected walking speed, was study in the experiments. In the PD diagnosis, a classification accuracy of 84.6 %, with a precision of 0.923 and a recall of 0.800, was achieved by the Naïve Bayes algorithm. We found four significant gait features in PD diagnosis: step length, velocity and width, and step width variability. As to the PD stage identification, the Random Forest outperformed the other studied ML algorithms, by reaching an Area Under the ROC curve of 0.786. We found two relevant gait features in identifying the PD stage: stride width variability and step double support time variability. The results showed that the studied ML algorithms have potential both to PD diagnosis and stage identification by analysing gait parameters. [Display omitted] •Step length, velocity, width, and width variability may distinguish PD vs control.•Variability of stride width and double support time may identify the PD stage.•Machine learning of gait parameters may support identification and assessment of PD.